Characteristics of Students with Disabilities, Parents, Teachers in Sexual Violence Prevention Education - Ayu Nabilla Azaara; Meri Neherta; Lili Fajria (GLOBAL HEALTH SCIENCE GROUP, 2024)
This study aims to identify the characteristics of students with disabilities, as well as the role of parents and teachers in the prevention of sexual violence in extraordinary schools in Bengkulu City. The method used is qualitative descriptive, involving students with disabilities, parents, and teachers in SLBN 1 and SLBN 4 Bengkulu City. The number of samples in this study was 214 people using the purposive sampling technique was selected to ensure the participation of relevant individuals. Data were collected through semi-structured interviews and observations, and then analyzed thematically to identify key themes. The results showed that the majority of respondents with disabilities were in grade VI, with variations in the types of mild and moderate disabilities. The role of parents, especially housewives with high school education, is very influential in supporting sexual education programs. On the other hand, teachers who have a S1 education and work as civil servants are key actors in the implementation of this education, although they still face challenges such as the lack of special training. The use of interactive educational media, such as animated videos, has been identified as an effective tool in improving the understanding of students with disabilities. The study concludes that collaboration between students, parents, and teachers is essential for the success of sexual violence prevention programs. The recommendations submitted include increasing teacher training and developing educational materials that are in accordance with the cognitive needs of students with disabilities. A holistic approach involving schools, families, and communities is also recommended to create a safe and supportive learning environment.